Eagle's syndrome with facial palsy - Mohammed Al-Hashim; Nasser Al-Jazan; Abdulrahman Abdulqader; Mohammed Al-Ghamdi (Wolters Kluwer Medknow Publications, 2017)
Eagle's syndrome (ES) is a rare disease in which the styloid process is elongated and compressing adjacent structures. We describe a rare presentation of ES in which the patient presented with facial palsy. Facial palsy as a presentation of ES is very rare. A review of the English literature revealed only one previously reported case. Our case is a 39-year-old male who presented with left facial palsy. He also reported a 9-year history of the classical symptoms of ES. A computed tomography scan with three-dimensional reconstruction confirmed the diagnoses. He was started on conservative management but without significant improvement. Surgical intervention was offered, but the patient refused. It is important for otolaryngologists, dentists, and other specialists who deal with head and neck problems to be able to recognize ES despite its rarity. Although the patient responded to a treatment similar to that of Bell's palsy because of the clinical features and imaging, ES was most likely the cause of his facial palsy.